Investigation of Psychometric Characteristics of the Spiritual Resilience Scale in Individuals with Chronic Diseases in Türkiye - Özcan, Serpil (Journal of religion and health, 2026)
The purpose of this study was to investigate the legitimacy and dependability of "the Spiritual Resilience Scale" in Turkish among people who were suffering from chronic conditions.This study was conducted with 309 individuals who had chronic diseases hospitalized at X University Hospital between October and December 2023. The study data were collected face to face using the "Spiritual Resilience Scale". According to the findings, the content validity index of the scale was found to be 0.99, and the factor loads of the items ranged from 0.833 to 0.925. The Cronbach's alpha coefficient was found to be 0.919 for the "Spiritual Endurance" subscale, 0.892 for the "Spiritual Enterprise" subscale, and 0.880 for the "Redemptive Purpose" subscale, while the overall Cronbach's alpha for the entire scale was 0.932. The CFA showed that the Turkish version of the 9-item, 3-subdimensional Spiritual Resilience Scale was correct, with no changes to the original scale form. It also found that the fit index values were good.The Turkish version of "the Spiritual Resilience Scale" is a valid and reliable measurement tool for evaluating spiritual resilience in clinical practices for individuals with chronic diseases.